Assessing relevancy of ICT driven consumer empowerment for business - Pires, G.; Rita, P.; Stanton, J. (Global Business and Economics Anthology, 2010)
Consumer empowerment commonly focuses on the deliberate provision of power to consumers by business, often using information and communications technology (ICT) to support controlled, self-service initiatives driven by operational efficiency goals. An alternative focus has recently emerged in consumer markets: one where consumer empowerment is not delegated or controlled by business. This undelegated consumer empowerment is an unintended consequence arising from a combination of continued advances in ICT, global technological convergence and marketing strategies developed by business seeking to take advantage of the potential of globalisation using the Internet. Relevancy for business may depend on the competitive environment nature of the product and on other factors. Undelegated consumer empowerment and the associated empowerment process are examined, leading to a discussion of the types of issues a business needs to consider in assessing relevancy of ICT driven consumer empowerment.